Structural evolution and mechanical behavior of NbTiVZr high-entropy alloy fabricated by electrostatic levitation - Yongxia Fan; Yan Lin; Qingbo Ao; Jian Wang; Chun Li; Chong Wei; Jianzhong Wang (Journal of Materials Research and Technology)
NbTiVZr high-entropy alloy (HEA), renowned for high strength and low density, is a highly promising material for advanced aeroengines application. However, its practical application has been hindered by compromised mechanical properties stemming from pronounced elemental segregation during conventional solidification processes. The electrostatic levitation (ESL) technique, as a containerless solidification platform, enables deep undercooling (ΔT) conditions that effectively suppress elemental segregation during rapid solidification. In this study, the NbTiVZr HEA samples were solidified via ESL processing covering ΔT regimes from 83 to 425 K (0.21 Tm). The microstructures and the mechanical properties of undercooled samples were analyzed. The thermophysical parameters of NbTiVZr HEA, including density (ρ), the ratio of specific heat to emissivity (ξT) and thermal expansion coefficient (β) were tested. Results show elemental segregation in the NbTiVZr HEA gradually diminishes with increasing ΔT, leading to a more uniform distribution of elements within the NbTiVZr HEA. Significantly, the microstructure undergoes a remarkable transition from polycrystalline to single crystal structure with increasing ΔT. Upon undercooled at 146 K, the HEA exhibits the highest hardness of 5.54 GPa, the highest Young's modulus of 101.11 GPa. Notably, the HEA exhibits the hardness of 5.29 GPa, ductility reaches an impressive 50 % for the 380 K undercooled single-crystal NbTiVZr HEA, much higher than the conventional as-cast NbTiVZr HEA. The ρ and ξT of NbTiVZr HEA increases linearly with falling temperature, whereas its β demonstrates a linearly decreasing trend during cooling.